Environmental Pollutants and their Impact on Human Health: A Review - Ati, Estabraq Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
There are tens of thousands of chemicals used in industry, agriculture, and homes Hospitals, tanneries, animal transplants and foundries. The number of organic chemicals is estimated which is used in industry in developing countries with about 50,000 compounds and thousands of pesticides. It is used to weed and weed. The matter is more difficult to address the issue of chemical pollutants in terms of research or processing is the nature of this material. These materials do not fall within what scientists study where the conditions of different matter and the degree of its interaction with other and the products of its decomposition and its impact on organisms extensively. Although these compounds have organic properties, they cannot be analyzed with enzymes, for example, because most of them are organic compounds of the original hydrogen atoms chemical groups, and thus lost the property of the original organic materials if their origin was sugars or amino acids, or others, which is why it does not apply to known organic laws interaction, decomposition and others.